2015
DOI: 10.1166/jbt.2015.1326
|View full text |Cite
|
Sign up to set email alerts
|

Ionized Ti Surfaces Increase Cell Adhesion Properties of Mesenchymal Stem Cells

Abstract: Titanium (Ti) surface topography of dental implants strongly influences osseointegration. To this view, in the present work we have analyzed the influence of an ionized titanium surface on stem cell adhesion properties. Human Dental Pulp Stem Cells (DPSCs) has been used in order to evaluate the influence of the ionized surface to the osteogenic commitment, extracellular matrix component production and cell adhesion molecules. The morphology of the cells grown onto this surface has been analyzed with SEM and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…Interestingly, as a result of this research, it has emerged that YB promotes cell differentiation through the activation of the NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) signaling pathway [35][36][37][38]. However, several differences have been pointed out between that study and our study.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Interestingly, as a result of this research, it has emerged that YB promotes cell differentiation through the activation of the NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) signaling pathway [35][36][37][38]. However, several differences have been pointed out between that study and our study.…”
Section: Discussioncontrasting
confidence: 57%
“…Pang and colleagues reported that YB powder is rich in calcium ions, and it is the main reason for its well-known hemostatic properties. In fact, calcium ions can stimulate the local production of hemostatic agents; moreover, the calcium ions interact with cytokines and growth factors, so stimulating the local bone formation [32][33][34][35]. Mesenchymal stem cells (MSCs) are located in several areas of the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation rate was investigated through the MTT-based assay according to the method previously described [81]. Briefly, 2 × 10 4 cells at p1, p3, and p5 were seeded onto 24-well plates in BM.…”
Section: Methodsmentioning
confidence: 99%
“…The mutagenic potential of experimental and control Ti implants was evaluated with the Ames test by using the Salmonella Mutagenicity Complete Test Kit (Moltox, Molecular toxicology Inc., Boone, NC, USA), as described in Ferroni et al [30] Briefly, Ti implants were extracted for (24 ± 2) h at (37 ± 1)°C, using nutrient broth (blank) as the extraction vehicle. The same extraction conditions were set for Aluminium oxide ceramic rod (VITA In-Ceram Alumina CA-12, CE 0124, lot 15,320) (negative control), and ICR 191 Acridine (Moltox, 60-101) and Sodium Azide (Moltox, 60-103) (positive controls).…”
Section: Ames Testmentioning
confidence: 99%